Effect of Systematic Risk on Stock Market Development in Indonesia: Moderating Role of Political Stability - Elmira Siska; Oyyappan Duraipandi (Proceeding of The International Conference on Economics and Business, 2023)
The objective of this study is to examine the effect of systematic risk which includes the exchange rate, rates of interest, inflation, and the stock market capitalization in Indonesia linked with political stability as moderating variable. This study is based on secondary data from the first quarter of 2000 until the last quarter of 2020. A quantitative research design with a descriptive approach was employed in this study. To avoid spurious regression, the stationary of the time series was checked by utilizing the Ng-Perron unit root test. To process the data, SPSS-25 and Eviews-10 programs were applied. According to the result of Ng-Perron test, the research’s variable is stationary at the first difference. The regression result confirmed that systematic risk, which consists of the USD exchange rate against the rupiah, interest rates, and inflation level have a negative impact on stock market development in Indonesia. Second, political stability plays an important role on the weakened negative impact of exchange rates, interest rates, and inflation on stock market development in Indonesia. The study recommends that the Indonesian government along with the public people must be able to maintain domestic political stability